Unfractionated heparin induced thrombocytopenia: A case review - Das, Vishnu; Fumilayo, Liza (Indian Journal of Case Reports, 2019)
Heparin-Induced Thrombocytopenia (HIT) is a disastrous, potentially devastating immune-mediated adverse drug reaction resultedin the formation of antibodies which activate platelets in the presence of heparin. Here, we presented an exemplifying case of a45-year-old male patient, a known case of Deep Venous Thrombosis admitted in Emergency Department with complaints of left groinpain along with passing bloody clot in urine for past 5 days. The patient was diagnosed as Renal Artery Thrombosis with the helpof radiological findings and was treated with Inj. Heparin. Thrombocytopenia developed on the first day of therapy and confirmedwith Heparin PF4 IgG ELISA Immunoassay. The patient switched to inj. Argatroban and later changed to oral anticoagulant therapy.Platelet count gradually came to normal upon stoppage of Inj. Heparin. To avoid a catastrophic outcome, heparin should be stoppedbefore initiating proper management.